Inculcation Religiosity in Preschoolers Local content curriculum - Munadi, Muhammad; Rahayu, Watik (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
Millennial era life is a big challenge, humans need a strong footing to face all the problems. Religion is God's guidance that becomes the handle of life and it is important to instill religious beliefs early on. The purpose of this study was to find the cultivation of religiosity in preschool children in Kindergarten Aisyiyah Branch and Kindergarten Santa Maria in Kartasura Regency. This study uses qualitative methods with data collection tools, namely interviews, direct observation, and document analysis. Data validated using triangulation of methods and sources. The results showed that the religiosity of planting in the TK Aisyiyah Kartasura branch had more burdens than in the Santa Maria Kindergarten. While its nature is more balanced between vertical ritual content and horizontal content in TK Aisyiyah Kartasura branches compared to TK Santa Maria. The cultivation of moral education is carried out through a step-by-step process starting with teaching to say and answer greetings (Islam), saying good morning and evening to non-Muslims and inviting children to always pray in every activity. Vertical ritual planting in TK Aisyiyah Kartasura branch has more burden through the practice of prayer, memorizing prayers and memorizing short letters from the Qur'an all in Arabic compared to TK Santa Maria only emphasizes the memorization of prayer in Indonesian. Keywords: Inculcation religiosity, Pre-schoolers, Local content curriculum References: Adams, K., Bull, R., & Maynes, M. L. (2016). Early childhood spirituality in education: Towards an understanding of the distinctive features of young children’s spirituality. European Early Childhood Education Research Journal, 24(5), 760–774. https://doi.org/10.1080/1350293X.2014.996425 Arce, E.-M. (2000). Curriculum for Young Children: An Introduction. (New York: Delmar Thomson Learning. Banerjee, K., & Bloom, P. (2015). “Everything Happens for a Reason”: Children’s Beliefs About Purpose in Life Events. Child Development, 86(2), 503–518. https://doi.org/10.1111/cdev.12312 Benson, P. L., Scales, P. C., Syvertsen, A. K., & Roehlkepartain, E. C. (2012). Is youth spiritual development a universal developmental process? An international exploration. Journal of Positive Psychology, 7(6), 453–470. https://doi.org/10.1080/17439760.2012.732102 Bridges, L. J., & Moore, K. a. (2002). Religion and Spirituality in Childhood and Adolescence. Child Trends, 1–59. Retrieved from http://www.childtrends.org/wp-content/uploads/2002/01/Child_Trends-2002_01_01_FR_ReligionSpiritAdol.pdf Davies, T. (2019). Religious education and social literacy: the ‘white elephant’ of Australian public education. British Journal of Religious Education, 41(2), 124–133. https://doi.org/10.1080/01416200.2017.1324758 Departemen Pendidikan dan Kebudayaan Depdikbud. (2007). Pedoman Teknis Penyelenggaraan Pos PAUD:(Direktorat PAUD, 2006) Direktorat PAUD Grand Design Program Pendidikan Anak Usia Dini Non- formal tahun 2007-20015. Indonesia. Eva L., E. (2013). Introduction to Early Childhood Education. Belmont: Wadsworth. Fisher, J. (2013). Assessing spiritual well-being: Relating with God explains greatest variance in spiritual well-being among Australian youth. International Journal of Children’s Spirituality, 18(4), 306–317. https://doi.org/10.1080/1364436X.2013.844106 Granqvist, P., & Nkara, F. (2017). Nature meets nurture in religious and spiritual development. British Journal of Developmental Psychology, 35(1), 142–155. https://doi.org/10.1111/bjdp.12170 Heiphetz, L., Lane, J. D., Waytz, A., & Young, L. L. (2016). How Children and Adults Represent God’s Mind. Cognitive Science, 40(1), 121–144. https://doi.org/10.1111/cogs.12232 Henderson, A. K. (2016). The Long Arm of Religion: Childhood Adversity, Religion, and Self-perception Among Black Americans. Journal for the Scientific Study of Religion, 55(2), 324–348. https://doi.org/10.1111/jssr.12262 Holloway, S. D. (1999). The Role of Religious Beliefs in Early Childhood Education: Christian and Buddhist Preschools in Japan. ERCP Early Chilhood Research and Practice, 1(2). Retrieved from http://ecrp.illinois.edu/v1n2/holloway.html Kienstra, N., van Dijk-Groeneboer, M., & Boelens, O. (2018). Religious-Thinking-Through Using Bibliodrama: An Empirical Study of Student Learning in Classroom Teaching. Religious Education, 113(2), 203–215. https://doi.org/10.1080/00344087.2017.1403788 King, U. (2013). The spiritual potential of childhood: Awakening to the fullness of life. International Journal of Children’s Spirituality, 18(1), 4–17. https://doi.org/10.1080/1364436X.2013.776266 Rissanen, I., Kuusisto, E., Hanhimäki, E., & Tirri, K. (2018). The implications of teachers’ implicit theories for moral education: A case study from Finland. Journal of Moral Education, 47(1), 63–77. https://doi.org/10.1080/03057240.2017.1374244 Scott, K. (2014). Inviting young adults to come out religiously, institutionally and traditionally. Religious Education, 109(4), 471–484. https://doi.org/10.1080/00344087.2014.924790 Suyadi, Destiyanti, A. Z., & Sulaikha, N. A. (2019). Perkembangan Nilai Agama-Moral Tidak Tercapai pada Anak Development of Religious-Moral Values Not Reached in Basic Age Children : A Case Study in Class SD Muhammadiyah. 6(1), 1–12.